PENGARUH PENGANGGURAN DAN INFLASI TERHADAP KEMISKINAN DI INDONESIA - Erika Feronika Br Simanungkalit (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to determine the effect of unemployment and inflation on poverty in Indonesia from 2007-2022. The research method is quantitative research with data analysis techniques using Multiple Linear Regression. The results showed: 1) Poverty is positively and significantly influenced by unemployment, 2) Poverty is positively and significantly influenced by inflation, and 3) Poverty is positively and significantly influenced by unemployment and inflation simultaneously, 4) Based on the test of the coefficient of determination, poverty is simultaneously affected by unemployment and inflation by 87.6% while the remaining 12.4% is influenced by other variables. Keywords: Inflation; Unemployment; Poverty